Türkiye ve Avrupa’da okul öncesi eğitim ekonomisinin karşılaştırmalı analizi - Bildirici, Zeynep (My University, 2017)
ÖZETTÜRKİYE VE AVRUPA’DA OKUL ÖNCESİ EĞİTİM EKONOMİSİNİN KARŞILAŞTIRMALI ANALİZİÜlkelerin toplumsal kalkınma hamleleri onları refah seviyesi daha yüksek bir geleceğetaşımaktadır. Bu açıdan eğitimine, özellikle okul öncesi dönemde önem veren ülkelerinkalkınma hamleleri de kuvvetli olmaktadır. Bu dönemde verilen eğitimin ilerikiyaşlarda daha da katlanarak toplumsal kalkınmada etkisini gösterdiği uluslararasıkuruluşların raporlarında sıklıkla vurgulanmaktadır. Bu nedenle, okul öncesi eğitimdeAB ülkeleri ile Türkiye’nin “Okul Öncesi Eğitim Ekonomisinin Karşılaştırmalı Analizi”bu araştırmayla ortaya konulmuştur.

Community development moves of countries carry them into a future with ahigher welfare level. In this respect, development moves of countries paying attention tothe education, particularly to the preschool education, are being stronger. It is frequentlyemphasized in the reports of international organizations that education given in thisperiod shows its effect by doubling in community development in the further ages.Therefore, “Comparative Analysis of Preschool Education Economy” of EU countriesand Turkey in preschool education is revealed out in this research. Data, reports,documents, by-laws, guidelines and information in official gazettes of institutions andorganizations such as UNESCO, UNICEF, BM, OECD and World Bank are examinedwith screening method in this research, which is made with a descriptive method, andgathered data is tried to be interpreted with comparative analysis technique.
Keywords: Avrupa; early childhood education; education economy; Eğitim (Okul öncesi); Eğitim ekonomisi; Ekonomik yönler; erken dönem çocuk eğitimi Preschool; Okul öncesi; Türkiye